The 19th Century of Islamic Education in Java (Historical Perspective of Pesantren Education Concept) - Aufi, Ahmad Umam; Rahmah, Yulinar Aini (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
Social and religious changes in the 19th century in Java were an important era in the history of Islamic education, especially pesantren in Indonesia. The aim of this research are to find out the condition and the model of pesantren in 19th century. The research method used is library research. The data were collected by the method of documentation then the data were analyzed using historical interpretation analysis (analysis-synthesis). The findings of this research are 1) the current of modernity movement and the emergence of Tarekat Naqsyabandiyah which was more Fiqh-oriented influenced the educational process in pesantren which taught a lot of Fiqh, 2) pesantren in the 19th century had seeds of how democracy in education, independence, skills education, national education and love for land and water, could be developed for the benefit of education today.